The structure of dyadic conversations and sex differences in social style - Grainger, A; Dunbar, R; Dunbar, R (Akadémiai Kiadó, 2009)
Verbal and non-verbal vocal cues of co-operation and competition were assessed in 120 freely-formed dyadic conversations. In line with previous research, female/female dyads were found to be the most cooperative. However, in female/female conversations, cooperation decreased, and non-verbal competition increased, when males were present. Male/male conversation did not exhibit significant changes in style when a female audience was present. Mixed-sex conversations showed evidence of compromise between the two conversational styles; however, females were still significantly more cooperative in conversational style than males, and males exhibited higher levels of verbal competitiveness than females. © 2009 Akadmiai Kiad.